Software quality testing process analysis - Mera Paz, Julián Andrés (Ingeniería Solidaria, 2016)
Introduction: This article is the result of reading, review, analysis of books, magazines and articles well known for their scientific and research quality, which have addressed the software quality testing process. The author, based on his work experience in software development companies, teaching and other areas, has compiled and selected information to argue and substantiate the importance of the software quality testing process.Methodology: the existing literature on the software quality testing process was analyzed at a local, national and global context. The ScienceDirect, Elsevier, Springer, Wiley Online Library, Proquest, Engineering Village, Scopus, Dialnet databases were thoroughly reviewed. Results: important concepts are described in the testing process, characteristics, methodologies and frameworks focused on the proper implementation of a testing process.Conclusions: The Article gives rise to results and conclusions in order for software product development companies to improve performance, effectiveness and optimization of software quality testing processes, and it is also a fundamental base to undertake software quality research processes.
Keywords: quality; test design; test tools; test levels; software; testing